Exploring the dynamics of Programmed Death-Ligand 1 in canine lymphoma: unraveling mRNA amount, surface membrane expression and plasmatic levels - Ubiali, Alessandra; Cesar Conti, Luiza; Dall’Ara, Paola; De Maria, Raffaella; Aresu, Luca; Moretti, Pierangelo; Sini, Federica; Riondato, Fulvio; Stefanello, Damiano; Comazzi, Stefano; Martini, Valeria (Frontiers in Veterinary Science, 2024)
Introduction. Programmed Death-Ligand 1 is a well-known immune checkpoint molecule. Recent studies evaluated its expression in different canine cancer types through different laboratory techniques. The present study aims to evaluate the surface membrane protein expression (mPD-L1) by means of flow cytometry (FC) in different canine lymphoma immunophenotypes. Furthermore, in a subset of cases, mRNA and plasmatic soluble protein (sPD-L1) have been assessed in the same patient, and correlations among results from the three analyses investigated.Methods. Samples obtained for diagnostic purpose from untreated dogs with a confirmed lymphoma immunophenotype were included: surface protein was assessed via FC and quantified with median fluorescence index ratio (MFI ratio), gene expression was evaluated by real time quantitative polymerase chain reaction (RT-qPCR) and plasmatic concentration of soluble protein (sPD-L1) measured with ELISA. Statistical analyses were performed to investigate any difference among FC immunophenotypes, updated Kiel cytological classes, and in the presence of blood infiltration.Considering FC, most B-cell lymphomas (BCL) were positive, with higher MFI ratios than other subtypes (81%, median MFI ratio among positive samples = 1.50, IQR 1.21-2.03, range 1.01-3.47). Aggressive T-cell lymphomas had a lower percentage of positive samples (56%) and showed low expression (median MFI ratio in positive samples = 1.14, IQR 1.07-1.32, range 1.02-2.19), while T-zone lymphomas (TZL) were frequently positive (80%) but with low expression (median MFI ratio in positive samples = 1.19, IQR 1.03-1.46, range 1.02-6.03). Cellular transcript and sPD-L1 were detected in all samples, without differences among immunophenotypes. No correlation between results from different techniques was detected, but sPD-L1 resulted significantly increased in FC-negative lymphomas (p=0.023).Discussion. PD-L1 molecule is involved in canine lymphoma pathogenesis, with differences among immunophenotypes detected by FC. Specifically, BCL have the highest expression and aggressive Tcell lymphomas the lowest, whereas TZL need further investigations.